2022
DOI: 10.1155/2022/1842547
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Comparison of Classification Algorithms for Rose Plants

Abstract: One of the key roles of Botanists is to be able to recognize flowers. This role has become highly challenging given that the number of discovered flower types are nearing half a million. To support Botanists, Information Technology offers promising solutions. Specifically, machine learning techniques are intrinsically appealing due to being precise enough as required. To this aim, two observations on flower leaves are relevant and leverage flower identification: one, flower plants exhibit unique features in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The success rates for dead/alive plant detection for the LiDAR and light curtain sensors were 93.75% and 94.16%, respectively. Additionally, a few other studies have reported the application of machine vision approaches using different machine learning and deep learning methodologies for detecting and classifying different flower nurseries [ 71 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Sensing and Automation Technologies For Ornamental Cropsmentioning
confidence: 99%
“…The success rates for dead/alive plant detection for the LiDAR and light curtain sensors were 93.75% and 94.16%, respectively. Additionally, a few other studies have reported the application of machine vision approaches using different machine learning and deep learning methodologies for detecting and classifying different flower nurseries [ 71 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Sensing and Automation Technologies For Ornamental Cropsmentioning
confidence: 99%
“…The original classification of fresh-cut flowers is done manually [1], but owing to human subjectivity, visual fatigue, experience differences, and classification efficiency, it is difficult to meet the requirements of standardized production of freshcut flowers and cannot guarantee the efficiency, consistency, and stability of grade classification and quality evaluation of fresh-cut flowers. To effectively reduce the labor intensity of workers, manual intervention, and the loss of post-harvest processing of fresh-cut flowers, achieve high efficiency and quality, and meet the demands of automatic processing and classification line of fresh-cut flowers, it is necessary to use automatic processing and classification systems [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Taking disease leaves of Chinese rose as the research object, Yin ( Yin et al., 2021 ) studied the feature extraction method from the disease region and proposed a flower disease classification model. Malik ( Malik et al., 2022 ) analyzed the performance of traditional classification methods, and provided a machine learning-based identification approach of rose types by leveraging the features from their leaves. Tigistu ( Tigistu and Abebe, 2021 ) studied a Chinese rose’s variety classification scheme using color and shape features, in which the color information was described by three statistical moments of the RGB, and the flower shape was described by Fourier coefficients.…”
Section: Introductionmentioning
confidence: 99%